2018
DOI: 10.1021/acs.langmuir.8b03153
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework MIL-101-NH2-Supported Acetate-Based Butylimidazolium Ionic Liquid as a Highly Efficient Heterogeneous Catalyst for the Synthesis of 3-Aryl-2-oxazolidinones

Abstract: A novel heterogeneous catalyst, the ionic liquid (IL) of 1-butyl-3-methylimidazolium acetate (BmimOAc) immobilized on MIL-101-NH2, denoted as IL­(OAc–)-MIL-101-NH2, was prepared by the “ship-in-a-bottle” strategy. The IL of BmimOAc was prepared in the MIL-101-NH2 nanocages primordially, in which the condensation product of MIL-101-NH2’s amine group with 1,1′-carbonyldiimidazole (CDI) reacted with 1-bromo butane, and then the intermediate exchanged with potassium acetate. The structure and physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In 2019, Ji and co‐workers utilized the metal‐organic framework MIL‐101‐NH 2 ‐supported BmimOAc heterogeneous catalyst, for the effective synthesis of bioactive 3‐aryl‐2‐oxazolidinones (Scheme 35). [58] This excellent composite catalyst system significantly exhibited superior catalytic activity and wide substrate scope for the preparation of a wide range of N ‐aryl‐2‐oxazolidinones 122 with good to excellent yields. Importantly, it can be recycled up to six times without obvious loss of its activity.…”
Section: Synthesis Of 2‐oxazolidinonesmentioning
confidence: 99%
“…In 2019, Ji and co‐workers utilized the metal‐organic framework MIL‐101‐NH 2 ‐supported BmimOAc heterogeneous catalyst, for the effective synthesis of bioactive 3‐aryl‐2‐oxazolidinones (Scheme 35). [58] This excellent composite catalyst system significantly exhibited superior catalytic activity and wide substrate scope for the preparation of a wide range of N ‐aryl‐2‐oxazolidinones 122 with good to excellent yields. Importantly, it can be recycled up to six times without obvious loss of its activity.…”
Section: Synthesis Of 2‐oxazolidinonesmentioning
confidence: 99%
“…The catalytic activity is not only due to the metal but also its chemical state: acetate groups change the DRS properties and photocatalytic efficiency. Chong et al reported the contribution of acetate groups for reducing the band-gap and then on the shift of the wavelength toward higher values (visible regions) (Chong et al, 2019). Moreover, the dispersion of the Cd complex in the diesel phase under agitation may allow a better availability of catalytic sites.…”
Section: Influence Of the Radiation Sourcementioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, nanoparticles have been widely used as solid supports for the immobilization of homogeneous catalysts. [8][9][10] For example, silica materials, [11] polymers, [12] graphene oxide, [13][14][15][16] carbon nanotubes, [17] iron oxide, [18] ionic liquids, [19,20] boehmite nanoparticles, [21,22] biochar, [23] magnetic nanoparticles, [24][25][26] etc. were employed as support for the stabilization of homogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%